Two new species of Icaleptes (Opiliones: Laniatores: Icaleptidae) from Sierra Nevada de Santa Marta, Colombia - Pereira, Maria Paula; Porto, Willians; Moya-Guerra, Natalia Andrea De; Martínez-Hernández, Neis José; Pérez-González, Abel (Zootaxa, 2025)
The genus Icaleptes was proposed by Kury & Pérez-González in 2002 to accommodate a single Colombian species, Icaleptes malkini, collected in the southeastern slope of Sierra Nevada de Santa Marta, Cesar Department. In this study, we describe two new species for this previously monotypic genus collected on the northwestern slope of the Sierra Nevada de Santa Marta, in the department of Magdalena. The new species Icaleptes dimorphicus sp. nov. and Icaleptes armasi sp. nov. were included within Icaleptes based on external and genital similarities such as male scutum magnum continuously convex and lacking the sulci; pedipalps with highly reduced setae; chelicerae stout and unarmed with a low, wide bulla; capsula externa of the penis modified into a robust stragulum with two widely separated apical lobes and a wide capsula interna visible from the dorsal aspect with a well-developed parastylar collar. In contrast to Icaleptes malkini, the two new species have the ventral plate of the penis differentiated into two regions, which we interpreted here as a wide pergula basally and a short stout rutrum apically. The new species also have other remarkable sexual dimorphisms such as males with a strong protuberance on coxa IV, an arched movable finger in the chelicerae, and enlarged basitarsomeres on leg III. The modification of coxa IV in males is a strong diagnostic character that facilitates the identification of both new species. The description of two new species that are closely related to the type species Icaleptes malkini helps us to understand the morphological variation of the current concept of Icaleptidae.